2012
DOI: 10.1108/02640471211221340
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration and crowdsourcing

Abstract: Purpose -This study aims to understand key features of existing multilingual digital libraries and to suggest strategies for building and/or sustaining multilingual information access for digital libraries. Design/methodology/approach -A case study approach was applied to examine four American multilingual digital libraries: Project Gutenberg, Meeting of Frontiers, The International Children's Digital Library, and the Latin American Open Archives Portal. This examination used a framework derived from digital l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Currently, multinational corporations, libraries or information service institutions have to manage online information resources in multiple languages (Lesk, ). For building multilingual collection in digital library, some libraries involved staff even users (Budzise‐Weaver et al, ). Wu, He, & Lu's survey () showed that when accessing academic databases or web information, multilingual information is often required.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, multinational corporations, libraries or information service institutions have to manage online information resources in multiple languages (Lesk, ). For building multilingual collection in digital library, some libraries involved staff even users (Budzise‐Weaver et al, ). Wu, He, & Lu's survey () showed that when accessing academic databases or web information, multilingual information is often required.…”
Section: Introductionmentioning
confidence: 99%